PENGGUNAAN KULIT PISANG KEPOK (Musa acuminate) PADA AIR KOLONG YANG MENGANDUNG TEMBAGA (Cu) - Eka Suharliana; Umroh Umroh; Dwi Rosalina (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2016)
Kepok banana peels have pectin substances. It contains pectin galakturonik acid, arabinose, galactose, and rhamnosa which can bind Copper (Cu). The purpose of this study are to know contains of Cu in open pit water after being treated using kepok banana peels and to reveal water quality of open pit area compare with water quality standars class II. This study was conducted in April 2015 at the Laboratory of Aquatic Resource Management, Faculty of Agriculture, Fisheries and Biology. The research method used an experimental method. There are 3 treatments that is control, kepok banana peels of fresh and kepok banana peels of powder. Each treatments was repeated 3 times repetition. Kepok banana peelshave not been able to reduce of levels cooper in open pit water, be expected to have occured accumulate heavy metals in kepok banana peels. The results of the study showed that the kepok banana peels have not been able to reduce Cu in open pit water. Water quality measurements which is DO, BOD, pH and Cu are not suitable with water quality standards class II because the value of resulting water is below standard water quality class II.